Hubungan Perhatian Orang Tua Terhadap Motivasi Belajar Anak Dalam Mengerjakan Tugas Selama Pandemi di TK Harapan Bunda - Gjoer, Fadila Rahma; Rahmawati, Santi (Universitas Lampung, 2025)
Early childhood education is very important in starting learning in a child's life. Early childhood education is carried out through the provision of educational stimuli to help the physical and spiritual growth and development of children, as well as to prepare children to enter education at the next stage. All potential that children have will be developed in kindergartens. As in Harapan Bunda Kindergarten, every day the children will be guided to learn and develop their potential. However, when the Covid 19 pandemic spread in Indonesia, children had to study boldly at their respective homes in accordance with government policies. Children will carry out learning boldly with guidance from parents and directions from the school. The role of parents becomes very important in this courageous learning. Parents' attention to children is one of the factors that must be considered in increasing early childhood learning motivation. In this study, the author will discuss the relationship between parental attention and children's learning motivation in carrying out assignments during a pandemic. To find out the significant influence of parental attention on the learning motivation of Harapan Bunda Kindergarten children, researchers used a quantitative approach with a correlational type of research, namely taking a sample of 34 students or all children attending Harapan Bunda Kindergarten. Data collection techniques to get about the variables of parental attention and learning motivation are by distributing questionnaires to all parents of Harapan Bunda Kindergarten students. From the data you will get how much influence parents' attention has on children's learning motivation during a pandemic at Harapan Bunda KindergartenKeywords: Early Childhood, Learning Motivation, Covid-19 Pandemic, Parental Attention.